Analisis Pengaruh Kualitas Audit Dalam Memoderasi Hubungan Kebijakan Dividen Terhadap Nilai Perusahaan - Cahyati, Rosi Annisa; Muhsin, Muhsin; Ikhsan, Syarbini (Politeknik Negeri Ambon, 2024)
In facing increasingly tight business competition, companies need to increase their economic value. One of the main factors is dividend policy, which is a strategic decision of the company. External factors such as audit quality also influence dividend policy. This research aims to evaluate the correlation between dividend policy, company value and audit quality in food and beverage sector companies on the Indonesia Stock Exchange during the 2020-2022 period. The research method used was purposive sampling and testing was carried out using Eviews 12. The results of the analysis show that the effect of dividends on company value is very small, but good audit quality can strengthen the relationship between dividends and company value in food and beverage companies listed on IDX during 2020-2022 period. The limitation of this research lies in the use of data that is limited to the food and beverage sector only. Therefore, suggestions and recommendations for further research are to conduct research with a wider sample and conduct longitudinal research to track the impact of dividend policy and audit quality on company value over time in a more comprehensive manner. Key words: dividend policy; company value; audit quality